2018
DOI: 10.1007/s10342-018-1108-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the roles of temperature, carbon inputs and airborne pollen as drivers of fructification in European temperate deciduous forests

Abstract: • We aimed at identifying which drivers control the spatio-temporal variability of fruit production in three major European temperate deciduous tree species: Quercus robur, Quercus petraea, and Fagus sylvatica. • We analysed the relations of fruit production with airborne pollen, carbon and water resources and meteorological data in 48 French forests over 14 years (1994-2007). • In oak, acorn production was mainly related to temperature conditions during the pollen emission period, supporting the pollen synchr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 96 publications
(147 reference statements)
5
39
2
2
Order By: Relevance
“…These results therefore suggest that the annual pollen amount, rather than pollen synchrony, determines pollination success and by extent fruiting success. Our results thus conflict with a recent work based on the same datasets than in our study (Lebourgeois et al 2018), in which the authors found no effect of annual airborne pollen amount on acorn production and concluded that their results supported the pollen synchrony hypothesis. However, their results and interpretation are questionable since they are drawn from poor estimates of pollen amount and synchrony at the fruiting sites (Appendix S2, and Table S4) and they did not directly test the effect of pollen synchrony on fruiting.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These results therefore suggest that the annual pollen amount, rather than pollen synchrony, determines pollination success and by extent fruiting success. Our results thus conflict with a recent work based on the same datasets than in our study (Lebourgeois et al 2018), in which the authors found no effect of annual airborne pollen amount on acorn production and concluded that their results supported the pollen synchrony hypothesis. However, their results and interpretation are questionable since they are drawn from poor estimates of pollen amount and synchrony at the fruiting sites (Appendix S2, and Table S4) and they did not directly test the effect of pollen synchrony on fruiting.…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to the work of Lebourgeois et al . () that was based on the same pollen and acorn datasets as in our study, we considered that the two datasets cannot be directly crossed. Indeed, based on their method we found that annual oak airborne pollen amount as well as pollen synchrony were poorly estimated at the acorn sites (Appendix and Table ).…”
Section: Methodsmentioning
confidence: 99%
“…However, results are broadly consistent between years, and the simulation confidence interval brackets the observation values ( Figure S1). Notice that leaf allocation is very consistent between years; however, observation of fruit production shows high variability, suggesting that the stem and fruit pool might be a buffer in the model or capture phenological interannual dynamics unrelated to climate (Lebourgeois et al, 2018), and these detailed physiological aspects are not captured by the model. Figures S2 and S3), along with the root and stem allocation factors, and the associated sensitivity of LAI.…”
Section: Simulation Of Energy Hydrological and Biomass Componentsmentioning
confidence: 99%
“…In some temperate angiosperms (e.g. deciduous oaks), the timing of flowering, which is closely related to the flushing-out of leaf buds (Franjic et al , 2011), influences the production of fruits (Lebourgeois et al , 2018; Schermer et al , 2019). This makes budburst an essential trait for the tree functioning, a trait subject to natural selection (Ducousso et al , 1996; Savolainen et al , 2007).…”
Section: Introductionmentioning
confidence: 99%